Peran Lembaga Keuangan Mikro Syariah dalam Pemberdayaan UMKM - Rahmad Bahagia; Ridwan Ridwan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
starting in early 2020, the world is shocked by the COVID-19 pandemic which has made the economy unstable again. This economic instability has an impact on all economic activities and business actors, including the MSME sector. The MSME sector began to experience anxiety in the middle of 2020. This anxiety was overcome by the existence of Islamic financial institutions that provided financial assistance programs with profit sharing that did not burden MSME actors. This study was conducted to see what the role of Islamic financial institutions in empowering MSMEs is. This research is a qualitative descriptive research that explains phenomena and data and previous research, then draws conclusions from the existing problems. The purpose of research using this method is to describe the problem taken more accurately and clearly based on the facts. Data collection is secondary data with journals, news, and government announcements which are analyzed and explained in the discussion. The results of the study explain that Islamic financial institutions are very helpful for MSMEs in obtaining funds for their operational activities through the KUR (People's Business Credit) program. Through Islamic financial institutions, MSMEs are also greatly helped by a profit-sharing system that does not burden business actors.